The Effect of Firm Characteristics, Political Connections, and Ownership Structure on Tax Avoidance: Evidence from Non-Cyclical Consumer Sector in Indonesia - Hanah, Siti; Febriansya, Agmal Revin; Asmilia, Nur (Indonesian Financial Review, 2025)
This study examines the effect of firm characteristics—profitability, leverage, and firm size—along with political connections and ownership structure (institutional and managerial ownership) on tax avoidance among non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using a panel data approach with 45 firm-year observations and regression analysis via E-Views 12, the results reveal that profitability and leverage negatively influence tax avoidance. However, firm size, political connections, institutional ownership, and managerial ownership show no significant individual effect. Collectively, these factors have a statistically significant impact. The study contributes to the literature by highlighting the multidimensional nature of tax avoidance behavior and its link to both internal and external corporate governance factors.